(untitled) - Vicki Hollett (Oxford, 1996)
The book is based on a carefully-constructed language syllabus, the fifteen units also tackle the key functional areas of business interaction, such as telephoning, meetings, and socializing
Keywords: english language - spoken english - problems, exercises, etc,english language - textbooks for foreign speakers,listening - problems, exercises, etc